Determination of Trace Chlortetracycline in Urine Using Phase-Separation Sublation and Ultraviolet Detection - Hou, Yanmin; Zhao, Xiaojun; Xie, Jimin (Asian Journal of Chemistry, 2014)
A novel analytical method is developed for the determination of trace chlortetracycline (CTC) in wastewater by phase-separation sublation coupled with an ultraviolet detector setting at 410 nm. Chlortetracycline can be transformed into tenary complex(Ni-CTC-DNA) in the presence of nickel(II) and deoxyribonucleic acid (DNA), which can be separated by phase-separation sublation easily. The optimum phase-separation sublation was performed on phase-separation reagent using 1 mol L-1 sodium chloride, caustic soda solution as acidity regulator and tetrahydrofuran (THF) as solvent. The linear regression equation is A = 8.33 × 105 C-0.0005, linear range is from 5.1 × 10-8-1.5 × 10-5 mol L-1, lower limit of detection (LOD) was 1.82 × 10-9 mol L-1. The recoveries of chlortetracycline in water samples were 99.1-101 %.